A Cultural History of Cuba during the U.S. Occupation, 1898-1902 - Iglesias Utset, Marial, 1961- (Book collections on Project MUSE., 2011)
In this cultural history of Cuba during the United States' brief but influential occupation from 1898 to 1902, a transitional period following the Spanish-American War, the author sheds light on the complex set of pressures that guided the formation and production of a burgeoning Cuban nationalism.